The Relationship between PM2.5 and Health Vulnerability in Argentina in 2010 - Bullo, Manuela (2023)
This study aimed to further explore the concept of health vulnerability in Argentina, including environmental pollution in 2010. To this end, we developed a geo-referenced database of PM2.5 concentrations and emissions data from the national emissions inventory to analyze possible correlations with the demographic, activity, education, and health data from the 2010 national census. In addition, to provide a more complete picture of health vulnerability in Argentina, an extended index (SVI + PM2.5) was constructed and mapped, including PM concentration. We obtained data for annual PM2.5 values emissions and air concentrations in Argentina from public sources (GEEA-AEIv3.0M for emissions and the Atmospheric Composition Analysis Group V5.GL.03 dataset for surface PM2.5). We evaluated health vulnerability using the “Sanitary Vulnerability Index” (SVI). PM2.5 emissions are concentrated in urban and intensive agricultural areas of Argentina. PM2.5 air concentrations were acceptable (≤10 µg/m3) in only 15% of the Argentinean territory. The newly developed SVI + PM2.5 index showed that exposure to particulate material significantly increases the vulnerability shown by SVI in almost all census blocks. These results indicate that the new SVI + PM2.5 index might help identify populations that are at risk because of social issues or air pollution.